The Application of Local Wisdom Management in Dayah Education: A Study of Dayah Jamiah Al-Aziziyah Bireuen: Penerapan Manajemen Kebijaksanaan Lokal dalam Pendidikan Dayah: Studi Kasus Dayah Jamiah Al-Aziziyah Bireuen - Sarayulis (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to examine the management of Islamic boarding schools (dayah) based on local wisdom at Dayah Jamiah Al-Aziziyah, Bireuen, Aceh. Employing a qualitative approach through a case study method, data were collected via in-depth interviews, participatory observations, and document analysis. The findings reveal that the management of the dayah is grounded in six core pillars: (1) charismatic leadership of ulama as the managerial axis, (2) decision-making through musyawarah (deliberation) reflecting traditional democracy, (3) discipline enforcement through exemplary conduct, (4) strong social relations between the dayah and the community as a source of legitimacy and support, (5) the use of kitab kuning (classical Islamic texts) as a traditional pedagogical system and a means for internalizing values, and (6) an adaptive management model that responds to contemporary challenges without compromising traditional identity. These findings both affirm and modify established theories such as charismatic leadership, communitarian democracy, social capital, and adaptive management by embedding them within a framework of spiritual and local values. The study proposes several theoretical contributions, including the concepts of spiritual-local leadership, deliberative spiritual governance, ta’dib-based discipline, embedded education institution, integrated adab-based curriculum, and transformative-local management. Thus, the dayah’s management based on local wisdom emerges as a contextual, sustainable, and character-oriented model for Islamic education.